An unusual case of stent thrombosis: a case report. Issue 3 (13th July 2019) - Rahman, Atifur; Wong, Sophia
Abstract: Background : Stent thrombosis is a serious and potentially life-threatening complication of percutaneous coronary intervention. It often presents dramatically, typically resulting in ST-elevation myocardial infarction which is associated with a high mortality rate. Premature discontinuation of antiplatelet therapy in the initial 30 days after stenting is arguably the most important predictor of stent thrombosis. In some cases, discontinuation of therapy is unintentional, such as in patients with short-bowel length or malabsorption syndromes. Case summary : A 70-year-old man presented to our hospital with stent thrombosis due to non-absorption of antiplatelet agents, 3 days after an elective percutaneous intervention to the right coronary artery. The patient, who had had a laparoscopic high anterior resection due to previous colorectal cancer, had noticed tablets passing whole into his colostomy bag. Repeat balloon angioplasty and stenting were performed and the patient received further antiplatelet therapy in a crushed form. Discussion : Drug absorption in the gastrointestinal tract is altered when a significant length of the gut has been resected. Reduced intestinal luminal transit time and insufficient contact time with intestinal mucosa leads to reduced bioavailability of drugs and increased risk of stent thrombosis. The aetiology of stent thrombosis can be investigated with intravascular imaging techniques and platelet function testing. Management includes using different drug formulations and doses and monitoring the outcomes of therapy. In some cases, it may also be appropriate to involve a gastroenterology team, preferably in the multidisciplinary environment of an intestinal rehabilitation centre.